Acquired appendiceal-cecal fistula as a complication of untreated acute appendicitis in a noncompliant patient: a case report - Mohammad AshrafAzimi; Abbas Abdollahi; Amir Rahmanian Sharifabad; Seyed Hassan Seyed Sharifi; Ali Mehri; Seyed Ramin Dabiri (Journal of Medical Case Reports)
Abstract Background Appendiceal fistula is a primary appendix perforation into the surrounding hollow viscera or skin and can rarely occur as a complication of appendicitis. To date, only nine cases of appendiceal fistula to the cecum have been reported. Case presentation We present the case of a 30-year-old Persian male who presented with a low-grade fever and lower abdominal pain for 3 days. He had a history of untreated acute appendicitis 3 years prior. During the appendectomy, a fistula between the appendix and cecum, along with a thick cecal wall, was found. The patient underwent a right hemicolectomy and was discharged with a diagnosis of appendiceal-cecal fistula in the context of appendicitis. Conclusion An appendiceal-cecal fistula usually does not cause any specific symptoms and is an accidental finding. Surgeons should thoroughly explore the ileocecal region for the fistula, particularly in patients with a history of untreated appendicitis. Although the appendiceal-cecal fistula is a rare finding, it can change the surgical plan. Therefore, it is important to discuss this complication with the patient and obtain informed consent preoperatively to avoid potential medicolegal issues. On the basis of our experience, right hemicolectomy is associated with a good surgical outcome in managing the fistula, especially when malignancy is suspected.